2012
DOI: 10.1111/j.1442-2050.2012.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial flora of the human oral cavity, and the upper and lower esophagus

Abstract: This reference study aims to survey the bacterial flora of the healthy lower human esophagus and to compare it with that of the upper esophagus and oral mucosa. The use of biopsies, in addition to brush samples, allows inclusion of not only transient bacteria present on the surface but also bacteria residing in the epithelia, and the yield of the two methods can be compared. Forty patients scheduled for surgery for reasons with no known influence on esophageal flora and with no symptoms or endoscopic signs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 30 publications
6
78
0
Order By: Relevance
“…revealed that Streptococcus viridans is the most frequent microorganism in both the normal esophagus and the oropharynx. These findings were consolidated by Norder Grusell et al.,35 who collected brush samples and biopsy samples from the esophagus, and reported the occurrence rate of Streptococcus viridans as 95‐98%. These studies support a possible correlation between the flora in the oropharynx and the esophagus.…”
Section: Microbiome Of the Normal Esophagusmentioning
confidence: 99%
“…revealed that Streptococcus viridans is the most frequent microorganism in both the normal esophagus and the oropharynx. These findings were consolidated by Norder Grusell et al.,35 who collected brush samples and biopsy samples from the esophagus, and reported the occurrence rate of Streptococcus viridans as 95‐98%. These studies support a possible correlation between the flora in the oropharynx and the esophagus.…”
Section: Microbiome Of the Normal Esophagusmentioning
confidence: 99%
“…As many as 700 different bacterial species colonizes in our mouth; unfortunately, the identity of many of them is still unknown (1,2). The complexity of biofilm greatly depends on the interspecies interaction during both early and maturing phases of biofilm formation.…”
mentioning
confidence: 99%
“…Streptococcus species are Gram-positive facultatively anaerobic cocci that are widely present in the oral cavity, occupying an established part of commensal flora (1). Infective endocarditis (IE) is characterized by formation of the vegetation that is a mass of platelets, fibrin, microcolonies of microorganisms, and inflammatory cells on the surfaces of the endocardium, particularly heart valves, and oral viridans streptococci are one of the major pathogens of IE (2).…”
Section: Genome Announcementmentioning
confidence: 99%